2004
DOI: 10.2298/tsci0402065b
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of co-pyrolysis of polyethylene/sawdust mixtures

Abstract: A study of the behavior of the thermal decomposition of mixtures of biomass and thermoplastics, such as polyethylene, is of interest for processes for the thermal recovery of industrial and urban wastes such as pyrolysis or gasification. No solid residue is formed during the thermal degradation of pure polyethylene. However, the addition of biomass, which generates char can vary the product distribution and increase the heating value of the gas obtained. A study of the thermal degradation of pine sawdust, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…Thus, enhanced rate of mass loss of biomass, reduced residue formation, and earlier degradation of HDPE bespeak for the synergistic effect of copyrolysis of HDPE biomass. Berrueco et al 24 reported the change in product distribution along with the enhancement in heating value of gas obtained by addition of pine sawdust in PE in a fluidized bed reactor. Similar studies for HDPE-JC and HDPE-KP are in progress.…”
Section: Thermal Degradation Of Mixturesmentioning
confidence: 99%
“…Thus, enhanced rate of mass loss of biomass, reduced residue formation, and earlier degradation of HDPE bespeak for the synergistic effect of copyrolysis of HDPE biomass. Berrueco et al 24 reported the change in product distribution along with the enhancement in heating value of gas obtained by addition of pine sawdust in PE in a fluidized bed reactor. Similar studies for HDPE-JC and HDPE-KP are in progress.…”
Section: Thermal Degradation Of Mixturesmentioning
confidence: 99%
“…In addition, Cornelissen et al [13] reported the reduction of water content in pyrolysis oil produced via the flash co-pyrolysis of biomass with polylactic acid. Berrueco et al [14] studied the co-pyrolysis of high density polyethylene mixed with sawdust in a fluidized bed reactor. The authors found a decrease in the concentration of oxygenated and aliphatic compounds in liquid fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contents of phenyl ring volatile and its derivatives for DEF are up to 42.28%, which could be from the pyrolysis of fluorenyl rings (as shown in Scheme ) due to instability of C 9 on fluorenyl ring, and a little bit cyclotrimerization [Scheme (a)]. Also identified products contained a few of naphthyl rings and their derivatives which were formed by Diels–Alder reaction [Scheme (b)]. Besides, a lot of phenanthryl ring volatiles and their derivatives were found in the pyrolysis products of DEF which could be produced by the reaction between fluorenyl rings and alkynyl units [Scheme (c)] .…”
Section: Resultsmentioning
confidence: 99%